Composition, functions, and applications of exosomal membrane proteins - Xu, Fang; Luo, Shumin; Lu, Pengpeng; Cai, Chao; Li, Weihua; Li, Chuanyun (Frontiers in Immunology, 2024)
Exosomes play a crucial role in various biological processes, such as human development, immune responses, and disease occurrence.The membrane proteins on exosomes are pivotal factors for their biological functionality. Currently, numerous membrane proteins have been identified on exosome membranes, participating in intercellular communication, mediating target cell recognition, and regulating immune processes. Furthermore, membrane proteins from exosomes derived from cancer cells can serve as relevant biomarkers for early cancer diagnosis. This article provides a comprehensive review of the composition of exosome membrane proteins and their diverse functions in the organism's biological processes.Through in-depth exploration of exosome membrane proteins, it is expected to offer essential foundations for the future development of novel biomedical diagnostics and therapies.